Hydrology drives variation in spawning phenologies and diversity of larval assemblages of Australian wet–dry tropical fish - Tyler, Kyle J.; Wedd, Dion; Crook, David A.; Kennard, Mark J.; King, Alison J. (Freshwater biology, 2021)
Setting ecologically based water‐extraction rules requires an understanding of the relationships between hydrology and the completion of aquatic organism life cycles. Successful reproduction of riverine fishes has been linked to hydrological variation across diverse climatic regions. However, the reproductive ecology for many species in wet–dry tropical northern Australia is poorly understood, and consequently there is little knowledge on how temporal (seasonal) and spatial hydrological variation influences fish reproduction in this region. This study aimed to quantify the hydrology‐related reproductive ecologies of freshwater fish across the wet–dry seasonal cycle and between differing hydrological classes in a northern Australian river (Daly River, Northern Territory) subject to increasing interest in water extraction. Sampling of larval and juvenile fish was undertaken over 1 year at eight sites classified into perennial and intermittent flow types. Fish spawning phenologies were developed and spatial–temporal dynamics in larval fish assemblages were investigated using model‐based multivariate and univariate analyses. Spawning occurred in all hydrological seasons, with low‐flow dry season periods identified as important for many fish taxa. For a different fish assemblage, spawning mostly occurred during high‐flow wet season periods. Larval assemblages in the wet season were more diverse than in the dry and wet–dry seasons. Perennial sites maintained higher diversity than intermittent sites year‐round; however, larvae were more abundant in intermittent sites for some taxa. Spatial and temporal differences in larval assemblages were largely explained by variation in the occurrence and relative abundance of three aseasonally spawning taxa (Craterocephalus spp., Melanotaenia spp. and Ambassis spp.) and the largely wet‐period spawning of Terapontidae spp. These results add to growing evidence of variation in spawning phenologies among fish species and the use of multiple hydrological phases for aseasonal reproduction. The diverse range of hydrological conditions used for spawning and rearing, and the differences between hydrological river classes among taxa, suggests that water‐extraction and environmental flow rules should aim to maintain hydrological conditions catchment‐wide during both low and high‐flow periods to reduce the risk of impacting fish reproduction. In particular, the results suggest that if perennially flowing sites began to flow intermittently, such as through over‐extraction of water or due to climate change, less diverse fish assemblages may result. This study expands our understanding of the relationships between hydrology and the reproductive ecology of freshwater fish in wet–dry tropical climates and may inform future ecologically based approaches to setting water‐extraction rules.